Caracterización básica de la limolita (formación las masas – Guayaquil) como material puzolánico y su influencia como aditivo en las propiedades del cemento tipo i - Hermenejildo, Andrea (2010)
In the cement Industry, raw materials are of great importance since they depend on the characteristics, development and optimization process for the manufacture of cement. The limestone and clay are essentially raw materials, but also requires natural or synthetic substances that give the concrete the required properties; these substances are called "additives." Additives are used primarily to improve the conditions of the concrete so that it becomes more suitable for working conditions or cheaper. Some additives utilities are to increase the workability, reduce water content, accelerate the development of resistance, increase strength, reduce or delay the development of heat, increase durability, reduce permeability to liquids, increase the adhesion of concrete with steel, etc. Among the additives are the pozzolan, their study is the main objective of this research which will develop the study of siltstone as pozzolanic material and its influence as an additive in the properties of cement Type I.